Preventive Effects of Different Doses of Pentoxyfilline Against CCl4-Induced Liver Toxicity in Rats - I. Abd Al-Zahra, Jameel; K. Ismael, Dawser; N. Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2017)
The liver protective effects of pentoxifylline were studied through pre-treatment of rats with various intraperitoneal (IP) doses (25, 50 and 100mg/kg/day) 14 days before induction of liver toxicity by carbon tetrachloride (CCl4). The parameters of oxidative stress, malondialdehyde (MDA) and reduced glutathione (GSH) were measured in liver homogenate in addition to histopathological examinations. Analysis of data revealed significant amelioration of oxidative stress in groups of animals pre-treated with different doses of pentoxifylline (PTX) compared to group of animals intoxicated by CCl4 as evidenced by lowering MDA contents and elevation of GSH levels in liver tissue homogenate but the levels still significantly different compared to controls. Additionally, increasing doses of PTX produce a dose-dependent improvement in liver tissue damage induced by CCl4, as evident histologically by the stained liver sections. In conclusion, these findings suggest that, the hepatoprotective effects of pentoxifylline are dose dependent.Key words: pentoxifylline, CCl4Â, liver toxicity.